Review Artikel: Pengaruh Sistem Emulsi Lipid terhadap Farmakokinetika Obat Lipofili - Ghina Salsabila; Candra Dwipayana Hamdin; Karlina Dwi Febrianingsih; Naya Wahyu Anindiya; Febriana Putri Rohmayani; Haulya Razkianita; Siti Maesarah; Sabila Rosyada; Puji Elok Dzakirah (Lembaga Pengembangan Kinerja Dosen, 2026)
Lipophilic drugs have low water solubility and often exhibit inconsistent absorption profiles, which can lead to suboptimal therapeutic outcomes in clinical use. Lipid-based drug delivery systems have emerged as a promising and widely studied formulation strategy because they are able to significantly enhance the solubility, bioavailability, and systemic distribution of lipophilic drugs. This study aims to identify how various lipid emulsion systems modify the pharmacokinetic profile of lipophilic drugs, compare the differences in effects among different types of emulsions, and highlight the key formulation characteristics that contribute to these pharmacokinetic parameter changes. The study was conducted through a comprehensive literature review of national and international scientific articles published between 2015 and 2025. The results indicate that lipid emulsion systems modify pharmacokinetics primarily through increased drug dissolution, accelerated absorption processes, reduced first-pass metabolism, and facilitation of lymphatic transport pathways. These mechanisms consistently result in increased Cmax, AUC, and overall bioavailability. The formulation characteristics that strongly influence these outcomes include nano-sized droplet distribution, lipid type selection, surfactant and co-surfactant composition, amorphous drug form, and the physical stability of the emulsion system.